Stakeholder-based sustainable management strategy in artisanal and small-scale gold mining: a case study of Sekotong, West Lombok, Indonesia - Ismayanti, Fairuz Luqyana; Suryaningtyas, Dyah Tjahyandari; Nuva, Nuva (Brawijaya University, 2025)
The management of Artisanal and Small-scale Gold Mining (ASGM) in Sekotong Sub-district, West Lombok Regency, encounters considerable challenges due to environmental and social repercussions. These situations indeed need to be restored by conducting the mining activities sustainably. This study examined stakeholders' interactions and influences in the context of sustainable ASGM management by employing the MACTOR method. MACTOR is a method used to identify key actors, relationships between key actors, and their strategic objectives. Research data were obtained from structured interviews and field data, which were then processed to identify each actor's level of influence and dependence in the management of ASGM Sekotong. The results of the analysis showed DESDM, DLH, DIKOP, and DIKES as actors with high influence and low dependence. Meanwhile, miners and cooperative administrators were actors who had high influence and high dependence on the management of ASGM Sekotong. In addition, the level of convergence between DESDM and UNDP showed a commitment to sustainable practices of ASGM Sekotong, while the divergence of DESDM and miners highlighted the challenges in the management of ASGM Sekotong in aligning the goals of economic development and preserving the environment. This study emphasized the importance of strengthening the role of actors with low influence and reducing their dependence on dominant actors. Strong alliances among actors are essential to support the sustainable management of Sekotong ASGM. These findings provide strategic insights to formulate more inclusive and sustainable Sekotong ASGM policies and practices.